2006
DOI: 10.1037/0022-0167.53.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Class jumping into academia: Multiple identities for counseling academics.

Abstract: Eleven counseling psychology and counselor education academics were interviewed regarding their experiences of progressing from lower-or lower-middle-class backgrounds to college and, further, to academic positions. Grounded theory method was used for data analysis, and consensual qualitative research methods were used for triangulation and data presentation. Participants described experiences of hardship as children, obstacles to advancement, resources that enabled academic pursuits, and thwarted belonging ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 31 publications
4
95
0
1
Order By: Relevance
“…Unfortunately, this position may be reinforced by the dearth of literature on the issue of psychologists' training, understanding, and personal experience in appreciating different social classes (Lott, 2002;Nelson et al, 2006;L Smith, 2005;Laura Smith, Foley, & Chaney, 2008), let alone the relation of class to theory and practice in vocational psychology specifically (Blustein, 2001; Autoethnography 21 Diemer & Ali, in press). To partly answer the challenge of the discipline's capacity to impact upon social class, in this paper we have introduced the qualitative research method autoethnography as a way to facilitate reflexive research and practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this position may be reinforced by the dearth of literature on the issue of psychologists' training, understanding, and personal experience in appreciating different social classes (Lott, 2002;Nelson et al, 2006;L Smith, 2005;Laura Smith, Foley, & Chaney, 2008), let alone the relation of class to theory and practice in vocational psychology specifically (Blustein, 2001; Autoethnography 21 Diemer & Ali, in press). To partly answer the challenge of the discipline's capacity to impact upon social class, in this paper we have introduced the qualitative research method autoethnography as a way to facilitate reflexive research and practice.…”
Section: Resultsmentioning
confidence: 99%
“…A number of scholars have suggested that practitioner training and learning is an ideal site at which to instill awareness of issues pertaining to social justice and class (Gainor, 2005;Hansen, 2003;Nelson et al, 2006;O'Brien, 2001;L Smith, 2005). Diemer and Ali (in press), for example, suggested that class and classism could be addressed in the process of training in career counseling.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…My own personal transition from working-class boy and labourer to psychologist and academic is reflected in the qualitative, grounded theory study of disadvantaged individuals who similarly made class-transitions into roles as counselling academics, with their concomitant development of bicultural and tricultural capacities (Nelson, Englar-Carlson, Tierney, & Hau, 2006). In my own case, I feel bicultural due to my capacity to speak and live the two dialects of rural working-class and metropolitan, educated middle-class.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from experiencing the problems of the poor in general, poor college youth have problems unique to their situation, such as a sense of isolation in college where others are more materially endowed, and disidentification with their less privileged social class as they become acculturated in a more educated class (Nelson, Englar-Carlson, Tierney, & Hau, 2006). Thus, it is possible that poverty-related stress mediates the effect of SES on wellbeing (Diemer, Mistry, Wadsworth, Lopez, & Reimers, 2013).…”
Section: Sense Of Poverty Mediates the Influence Of Family Ses On Psymentioning
confidence: 99%
“…While college affords poor youth the opportunity for socioeconomic advancement (Nelson et al, 2006), this does not always materialise, perhaps because material scarcity becomes insurmountable, or perhaps because a keen sense of poverty constrains one's capacities. Yet, there are social resources that could mitigate the effects of poverty, and of a sense of poverty, on youth's wellbeing.…”
Section: The Mitigating Role Of Family Problem-solving and Social Resmentioning
confidence: 99%